(untitled) (Acta Scientiarum. Agronomy, 2020)
Calcium (Ca2+) is a nutrient in tomato plants, of which deficiency usually causes several problems including a physiological disorder known as blossom-end rot (BER) in the fruit. The objective of this study was to evaluate and identify morphological and physiological characteristics related to the susceptibility of tomato varieties to BER. The varieties studied were ‘Amalia’, ‘IPA-6’, ‘M-82’, ‘Mara’, and ‘Nagcarlan’, presenting different fruit formats. Physiological parameters that negatively correlated with BER were plant water potential, leaf area, plant dry mass, relationship between proximal/distal Ca2+, K+ content in the proximal and distal portions of the fruit, and proximal Ca2+ content. Physiological parameters that positively correlated with BER were number of trichomes in the abaxial and adaxial leaf portions, leaf stomatal conductance, distal Ca2+ content bound to the cell wall, leaf transpiration, and fruit length. Our results showed that ‘Mara’ and ‘Nagcarlan’, ‘Amalia’ and ‘IPA-6’, and ‘M-82’ presented low, medium, and high susceptibility to BER, respectively. We also found that total fruit Ca2+ concentration, particularly in the distal fruit tissue, was not the only factor responsible for the development of BER; rather, the balance between factors that increase and decrease the susceptibility of each variety affected development of this disorder.